Impact of vegetarian diets on the environment - Marinova, Dora; Raphaely, T. (CRC Press, 2018)
This book describes issues of the vegetarian diet and outlines ways to prevent nutrient deficiencies. Vegetarian Nutrition and Wellness focuses on synthesizing research around vegetarian diets and human health.